CIRCULAR ECONOMY ‒ A PROMISING DIRECTION FOR THE DEVELOPMENT OF NEW TECHNOLOGIES AND PRODUCTS (INNOVATIVE ECONOMY, 2026)
Ternova A.S., Vlasenko I.H. CIRCULAR ECONOMY ‒ A PROMISING DIRECTION FOR THE DEVELOPMENT OF NEW TECHNOLOGIES AND PRODUCTSPurpose. The aim of the study is to consider the basic principles of the circular economy and the possibility of implementing them in the latest technologies for the production of goods.Methodology of research. General scientific methods were used in the research process: induction and deduction – to analyse individual methods of the circular economy and outline its general principles; cause-and-effect relationships – to predict the prospects for implementing the principles of the circular economy; analysis and synthesis – for a detailed analysis of individual components, their relationships and identifying the main trends in the development of the circular economy in the world and Ukraine; abstract and logical – to summarize information from scientific sources, form theoretical conclusions.Findings. The paper examines the capacity of the waste management market in Ukraine. The priority key value chains of products based on the EU Strategy in the main industries are analysed. Strategies for achieving the material goals of the circular economy – minimizing raw materials, restoring supporting ecosystems, and preventing material losses – are considered. It is shown that the implementation of circular economy principles has both certain risks and prospects. For Ukraine, the transition to a circular economy will be important both in terms of modernization and increasing added value, as well as increasing investments and strengthening cooperation with the EU at the international level. Important directions on the path to a circular economy for Ukraine are the creation of waste management models that meet EU requirements; the development of processing enterprises; and the integration of circular economy principles into the national recovery and development strategy.Originality. The understanding of trends in the implementation of circular economy principles in the modern world, as well as the perception of significant risks that may threaten the implementation of these principles, has further developed.Practical value. The results of the study can be used in shaping an enterprise's strategy for transitioning from a linear production model to a closed cycle, where the emphasis is on reuse, repair, shared consumption, product durability, and resource recovery.Key words: circular economy, waste management, minimization of raw materials, environmental friendliness, innovation.
Keywords: circular economy; waste management; minimization of raw materials; environmental friendliness; innovation